DRUGI KAO KONSTITUTIVNI ELEMENT SUBJEKTA: S. B. feat. S. B. (Philological Studies, 2019)
The short story „Svetislav Basara intervjuiše Semjuela Beketa za Treći program Radio-Beograda“ („Svetislav Basara Interviews Samuel Beckett on the Third Channel of the Radio Belgrade“ by David Albahari is the starting point of the analysis that questions the poetical connections of the Basara and Beckett's fiction. In so doing, the central interests are Beckett's novel „Molloy“ and Basara's fictions „Priče u nestajanju“ („Vanishing Stories“), „Kinesko pismo“ („Chinese Letter“) and „Peking by Night“. The article discusses the status of the selected concepts from Albahari’s short story (“shapelessness”, “speech”, “frame”, “rain”, “pause”, “monologue”, “dialog”, “silence”, “darkness”, “unvisited place”, “work” and “emptiness”) in the context of poetics by the given authors. On the abstract level, Basara’s „Priče u nestajanju“, „Kinesko pismo“ and „Peking by night“, just as Beckett’s „Molloy“, mediate existential convulsion of the subject faced with the emptiness and nothingness whereat the writing turns out to be the compulsion, but also the prolongation of death. Therefore, Basara’s fiction represents the rich potential for intertextual openness, which will be confirmed in the article with the additional comparative analysis on the concept of characters/storytellers.